FC082: Effects of Dapagliflozin in Patients with Chronic Kidney Disease According to Background Angiotensin-Converting Enzyme Inhibitor and Angiotensin Receptor Blocker Dose. (3rd May 2022) - Lambers Heerspink, Hiddo; Jong, Niels; Stefansson, Bergur; Chertow, Glenn; Maria Langkilde, Anna; Mcmurray, John; Correa-Rotter, Ricardo; Rossing, Peter; Toto, Robert; Wheeler, David
Abstract: BACKGROUND AND AIMS: Treatment guidelines for patients with chronic kidney disease (CKD) recommend renin–angiotensin system inhibition (RASi) with angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARBs) to reduce the risk of kidney failure. However, patients with more advanced CKD do not always tolerate RASi. The sodium-glucose cotransporter 2 inhibitor dapagliflozin reduced the risk of kidney failure in patients with CKD in the DAPA-CKD trial. We performed a post hoc analysis of this trial to assess the efficacy of dapagliflozin by baseline dose level of ACEi or ARB. METHOD: Participants with CKD [estimated glomerular filtration rate (eGFR) 25–75 mL/min/1.73 m 2 ; urinary albumin-to-creatinine ratio (UACR) 200–5000 mg/g), with or without type 2 diabetes, were randomized 1:1 to dapagliflozin 10 mg or placebo, once daily. Participants were to be treated with the recommended target dose, or a stable tolerated dose of ACEi or ARB, unless medically contraindicated, for ≥4 weeks prior to inclusion. The primary outcome was a composite of sustained ≥50% eGFR decline, end-stage kidney disease or death from a kidney or cardiovascular cause. A prespecified kidney-specific secondary outcome was the same as the primary endpoint, but without cardiovascular death. A composite cardiovascular outcome (heart failure hospitalization or cardiovascular death), and all-cause mortality were other secondary endpoints. Time-to-event analyses were performed to assess the effects of dapagliflozin versus placebo according to baseline prescription and dose of ACEi or ARB treatment. RESULTS: Of 4296 (99.9%) participants with available data on ACEi/ARB doses, 1231 (28.7%) were using the target dose, 1867 (43.5%) a dose ≥50% to <100% of target, 1068 (24.9%) a dose 0 to <50% of target and 130 (3.0%) were not using an ACEi/ARB. In the placebo group, the event rate for the primary outcome was highest among participants not using ACEi/ARBs compared to the other subgroups (figure 1 ). The benefit of dapagliflozin on the primary composite outcome was consistent regardless of use or non-use of the target dose of ACEi/ARBs. This consistency was maintained for the secondary outcomes (Figure 1 ). Dapagliflozin compared to placebo reduced the rate of eGFR decline over the study by –0.93 [95% confidence interval (95% CI) 0.61–1.25] mL/min/1.73 m 2 . This effect was present regardless of the use or non-use of target doses of ACEi/ARBs ( P for interaction 0.877). CONCLUSION: Dapagliflozin was similarly efficacious in reducing major adverse kidney and cardiovascular outcomes in participants with CKD regardless of the use or dose of ACEi/ARB.